REPRESENTASI KEMATIAN PADA MASA KOLONIALISME DALAM PUISI MENGHADAPI MAUT KARYA SUTAN TAKDIR ALISJABNA: KAJIAN POSKOLONIAL - Nensilianti, Nensilianti; Ridwan, Ridwan; Ardisa, Ardisa (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2024)
This research aims to explain the meaning of poetry during the colonial period contained in the poem Menghadapi Maut. The poem Menghadapi Maut by Sutan Takdir Alihsajbana is a poem that describes the social reality of Indonesia as a European colony. Almost three centuries of colonialism in Indonesia has had a huge impact on the lifestyle of the Indonesian people today, through the poem Menghadapi Maut, the struggles and conditions of the Indonesian people see and feel the anxiety of the end of life from the colonizers who are about to take their lives. Therefore, the purpose of writing this article is to provide an overview of the form of postcolonial facing death poetry. The research method uses a descriptive qualitative approach with a content analysis method, and the source of information is the poetry text by Sutan Takdir Alihsajbana Menghadapi Maut. The results of this study indicate that there is a representation of death addressed by Menghadapi Maut poem through anxiety and unrest facing the conditions of warfare during the colonial period. The conclusion of this research is the description of death in the poem "Menghadapi Maut" that occurred in the colonial era which is clearly interpreted as a form of anxiety and unrest facing death.